THU0690 DISEASE ACTIVITY CORRELATES WITH INSULIN RESISTANCE AND ADIPOCYTOKINES IN PATIENTS WITH DMARD-NAÏVE RHEUMATOID ARTHRITIS . (June 2019) - taylan, ali; Toprak, Burak; Akinci, Baris; Birlik, Merih; Arslan, Fatma Demet; Gundogdu, Baris; Colak, Ayfer
Abstract : Background: Cardiovascular events such as myocardial infarction and stroke are frequent comorbidities in rheumatic diseases [1]. In relation, components of the metabolic syndrome (MS) including insulin resistance (IR), central obesity, high blood pressure, high triglycerides, and low high-density lipoprotein (HDL) are related to a high rate of endothelial dysfunction and atherosclerosis in patients with RA [2]. Objectives: We aimed to investigate the relationship between disease activity and insulin resistance (IR) and the levels of adipocytokines in non-diabetic patients with newly diagnosed rheumatoid arthritis (RA) who are naïve to disease modifying anti-rheumatic drugs (DMARDs). Methods: Forty-seven DMARD-naïve patients with RA and 25 age-, gender-, and BMI-matched controls were included. Erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), 28-joint-count disease activity score (DAS28), serum lipids, glucose, HbA1c, insulin, leptin, resistin, visfatin, and RBP4 levels were measured. Homeostasis model assessment for insulin resistance (HOMA-IR) was calculated. Patients were studied before and 3 months after treatment with DMARDs. Results: Levels of adipokines were similar in patients with RA and controls (p > 0.05 for all). However, RA patients with active disease (DAS28 > 3.2) had numerically higher levels of leptin (9.3 (3.7-17.4) vs. 7.6 (3.7-11.0), p = 0.289), insulin (8.0 (5.2-12.7) vs. 5.9 (4.2-8.7), p = 0.285), and HOMA-IR (1.9 (1.1-3.0) vs. 1.3 (1.0-1.9), p = 0.209). DAS28 was correlated with HOMA-IR (r = 0.356, p = 0.016), insulin (r = 0.323, p = 0.02), and leptin (r = 0.399, p = 0.005) in the study group (Figure-1 ). Regardless of the type of treatment modality, leptin levels (7.4 (4.4-13.4) vs. 6.4 (3.3-11.6, p = 0.047) decreased significantly after treatment, as did insulin levels (6.9 (4.9-12.5) vs. 5.9 (4.1- 8.8), p =0.01) and HOMA-IR score (1.7 (1.1-2.7) vs. 1.3 (1.0-2.0), p= 0.012). The reduction in leptin was more prominent in patients with active disease (9.3 (3.7-17.4) vs. 6.9 (3.1-11.4), p = 0.028). The reduction in ESR was correlated with ΔHOMA-IR (r = 0.308, p = 0.039), and CRP reduction was correlated with Δresistin (r = 0.288, p = 0.049) and ΔRBP4 (r = 0.456, p = 0.001). Conclusion: Disease activity is associated with IR and correlates with circulating levels of adipokines in patients with RA. Treatment with DMARDs reduces leptin and improves IR. References: [1] Maradit-Kremers H, Crowson CS, Nicola PJ, Ballman KV, Roger VL, Jacobsen SJ et al. Increased unrecognized coronary heart disease and sudden deaths in rheumatoid arthritis: a population-based cohort study. Arthritis Rheum.2005; 52:402–11. [2] Burggraaf B, van Breukelen-van der Stoep DF, de Vries MA, Klop B, van Zeben J, van de Geijn GM et al. Progression of subclinical atherosclerosis in subjects with rheumatoid arthritis and the metabolic syndrome Atherosclerosis. 2018; 271:84-91. Disclosure of Interests: None declared